Computer Games as Learning Tool towards Children Road Safety Education - Hussin, Masnida; Hanis Mohd Fouzi, Nor (International Journal of Engineering and Technology, 2018)
Road safety awareness is one of the many awareness programs that are often highlighted and discussed around the world. The road accident statistics are increased due to the lack of exposure and awareness among communities about traffic environments and rules. Children are one of the most vulnerable populations involved in traffic accidents. The children are unable to familiarize themselves with the surroundings, especially when crossing the road. This research attempts to improve road-safety awareness among children by using computer games as a learning tool. Specifically, it determines the progress of knowledge on the road rules and conditions after the children using the tool. The computer online game is suitable methods to use for teaching them on road safety due to interactive application always intimate the children. Besides the survey questions that related to road traffic rules, we also measures the attitude towards road safety in the participant (i.e., children and adult). Descriptive analysis in frequency, mean, and percentage are used to describe the respondent’s information. Statistical Package for Social Science (SPSS) is used to analyze the findings. The overall findings show that all respondents have positive feedback on online games as a road safety tool. Interestingly, the significant output shows on the different knowledge about road safety when the children are analyzed for before and after they played the games. The future research is suggested to study the other group of participant as the respondent in this work is limited to the primary school children. It can be improved by involving the large sample size and wider location.